1999
DOI: 10.1111/j.1532-5415.1999.tb01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Urge Incontinence: New Health‐Related Quality of Life Measures

Abstract: The newly developed Urge-Incontinence Impact Questionnaire and Urge-Urinary Distress Inventory are reliable, and evidence of validity was found in a diverse population. These instruments are available for use in trials of new therapeutic interventions for urge incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 20 publications
(23 reference statements)
4
47
0
Order By: Relevance
“…Even though UI prevalence rates vary according to the definition and characteristics of the studies and target populations 15 , it is estimated that 8 to 58% of adult women 1 have symptoms of incontinence 16,17 . Estimates show that OB affects approximately 40% of the women who seek medical treatment for UI 18 . In Brazil, almost 10% of women who visit the gynecologist have urine loss as the main complaint 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Even though UI prevalence rates vary according to the definition and characteristics of the studies and target populations 15 , it is estimated that 8 to 58% of adult women 1 have symptoms of incontinence 16,17 . Estimates show that OB affects approximately 40% of the women who seek medical treatment for UI 18 . In Brazil, almost 10% of women who visit the gynecologist have urine loss as the main complaint 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Some measures are genderand condition-speci¢c, such as the prostate-speci¢c module of the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 core questionnaire [Joly et al, 1998], the Incontinence Impact Questionnaire (IIQ-7), a 7-item self-reporting instrument designed to assess the impact of urinary incontinence (UI) in males [Moore and Jensen, 2000], and the Urge-Incontinence Impact Questionnaire [Brown et al, 1999], Urge Impact Scale (URIS) [DuBeau et al, 1999], and Urogenital Distress Inventory [Shumaker et al, 1994], which are speci¢c to females and condition. Still others measure speci¢c areas of impact: the Dowell-Bryant Wilcoxon signed ranks, P ¼ 0.00.…”
Section: Gendermentioning
confidence: 99%
“…Regardless of its cause, incontinence usually has a signi¢cant adverse e¡ect on health-related quality of life. Because a primary goal of treating urinary incontinence is to improve quality of life, there are a number of condition-, gender-, and age-speci¢c clinical outcome measures in the literature [Lee et al, 1995;Joly et al, 1998;Brown et al, 1999;Dowell et al, 1999;DuBeau et al, 1999;Moore and Jensen, 2000]. However, there is a need for a broad, uniform quality of life score validated across a diverse patient population, including both genders, all age ranges, and those treated either medically or surgically.…”
Section: Introductionmentioning
confidence: 98%
“…Although it is defined as DO in the absence of a definite cause, some authors have reported on the presence of neurological signs (7). Despite the fact that not all individuals with idiopathic overactive bladder require treatment, the condition has been shown to significantly impact on patient quality of life; often leading to isolation and depression (8,9).…”
Section: Introductionmentioning
confidence: 99%